Evaluating Budget Functions for Effective Revenue and Expenditure Planning in Hulu River South District - Hikmahwati; Nadhilah, Gina; Nikmah, Nailiya (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The public sector budget has a function as a local financial management planning tool. BPKPD district of Hulu River South is an institution that carries out the duties of the local government in the planning of the regional budget. This study is aimed at finding out the application of budget functions as a tool for planning income and expenditure in the BPKPD district of Hulu River South. This study uses a method of quantitative research using a descriptive approach. The study uses three types of measurement analysis to find out the use of budget function as a planning tool, namely, the process of budgeting, the level of effectiveness of budget income, and the degree of efficiency as well as deviations in budget expenditures. The income budget effectiveness rate for 2022 reached 118.60% (more than 100%) with the category of highly effective, coming from three types of regional income. First, Regional Real Income with an efficiency ratio of 87.51% belongs to the effective category. Second, Transfer income with an effectiveness rate of 119.82% belonging to the highly efficient category. The calculation of the expenditure efficiency ratio showed less efficient access, with a ratio of 93.06%. Operations purchases obtained a rate of 75.92% in the efficient category. Capital purchases gained access to efficiency ratios of 91.41%, including the less effective category. Unexpected expenditures reached the rate of efficiency of 17.92%, in the highly efficient categories. Lastly, the transfer spending sector has an efficiency rate of 99.81% in the less efficient category. Secondly, the calculation of the variance analysis in the regional spending sector shows that the entire account in the local spending area has more variance. No spending account has a budget deficit as a result of the realization or achievement of greater income than estimated. The deviation that occurs on the entire account of the shopping sector is favorable.